Cell communication in health and disease : readings from Scientific American magazine - Rasmussen, Howard, 1925- (New York : W.H. Freeman and Co., 1991)
A collection of articles discussing three main areas of cell communications, the first focusing on the production of hormones by cells and organs and their effect on distant tissue, the second looking at the messenger systems within the cells, and the third studying disruption in cell communication can lead to disease.
Includes bibliographical references (p. [177]-179) and index.
Young Adult
Keywords: Cell interaction; Cell receptors; Cellular signal transduction; Second messengers (Biochemistry); Cells